Australia and the pursuit of "not undermining" regional bodies at the biodiversity beyond national jurisdiction negotiations. (February 2022) - Beringen, Ethan; Liu, Nengye; Lim, Michelle
Abstract: The United Nations General Assembly Resolution 69/292 formally established the negotiations on a new legally binding instrument for the conservation and sustainable use of marine biodiversity beyond national jurisdiction (BBNJ). This resolution stated that the instrument "should not undermine" existing bodies and legal instruments. While a consensus on the accurate legal interpretation of this requirement has largely eluded the delegations, it is rather how this directive is utilised by states within the negotiations that is most revealing. Specifically, this article will explore Australia's use of the "not undermining" directive at the BBNJ negotiations in order to further clarify its potential function. Of particular interest is how states may shape the direction of the negotiations to serve their policy interests through relying on the authority of this original directive. Australia's interests in Regional Fisheries Management Organisations (RFMOs) will serve as a case study when examining how this phenomenon plays out in practice. Ultimately, tentative answers to burning questions regarding "not undermining" will be determined based on Australian positions. These answers will be contrasted with the current BBNJ draft text in order to highlight how state interests at the negotiations will affect the meaning prescribed to the "not undermining" directive going forward.